2021
DOI: 10.3390/soilsystems5020027
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Contamination of Urban Soils—A Decade Study in the City of Lisbon, Portugal

Abstract: There is an intense and continuous growth of the world population living in cities. This increase in population means an increase in car traffic, an increase in new constructions and an increase in the production of waste that translates into an intensive use of land, particularly in terms of soil contaminants. Among other environmental contaminants, toxic metals, such as lead (Pb), cadmium (Cd), nickel (Ni) and chromium (Cr) represent a public health problem. In this study the content of toxic metals in Lisbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 56 publications
0
20
1
Order By: Relevance
“…When comparing results of PTEs content obtained in this research with results from our previous research [4,73], levels of Mn were found to be similar, but Cr, Cu, Ni, Pb, and Zn concentrations were higher. On the other hand, Cr, Cu, Pb, and Zn content in soils in Novi Sad [74], Lisbon [79], and Thessaloniki [73] was similar, but Ni was somewhat lower than the levels measured in this research (Table 2). Similarities in terms of PTE content were also found in soils from Šabac [75] and Kragujevac [76], where concentrations of most of the examined elements were similar to those determined in this research, with the exception of the higher content of Cr in Kragujevac and Mn in Šabac.…”
Section: Pseudo-total Content Of Selected Ptes In Examined Urban Soilscontrasting
confidence: 53%
“…When comparing results of PTEs content obtained in this research with results from our previous research [4,73], levels of Mn were found to be similar, but Cr, Cu, Ni, Pb, and Zn concentrations were higher. On the other hand, Cr, Cu, Pb, and Zn content in soils in Novi Sad [74], Lisbon [79], and Thessaloniki [73] was similar, but Ni was somewhat lower than the levels measured in this research (Table 2). Similarities in terms of PTE content were also found in soils from Šabac [75] and Kragujevac [76], where concentrations of most of the examined elements were similar to those determined in this research, with the exception of the higher content of Cr in Kragujevac and Mn in Šabac.…”
Section: Pseudo-total Content Of Selected Ptes In Examined Urban Soilscontrasting
confidence: 53%
“…The use of Igeo in the soils has been widely reported in literature recently, including Guangzhou-Foshan urban soils of South China [ 45 ], Anshan industrial city (Northeast China) [ 21 ], a municipal solid waste dump in Uyo (Nigeria) [ 49 ], ithallium mining area of southwest Guizhou (China) [ 50 ], Harran Plain (Turkey) [ 51 ], trailer park in Nigeria [ 28 ], Houzhai River Watershed of Guizhou Province (China) [ 46 ], wheat cultivated and natural soils of pastoral lands in the Bai Cheng Region (Xinjiang, China) [ 52 ], Zhundong mining area in Xinjiang [ 53 ], a Ramsar site (Deepor Beel) (Guwahati, India) [ 54 ], Panzhihua (China) [ 55 ], and the city of Lisbon (Portugal) [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…The use of ER and PERI has been widely reported in literature recently such as in polluted farmland soils from China [ 67 ], Guangzhou-Foshan urban soils of South China [ 45 ], Recife metropolitan region in Brazil [ 68 ], industrial area of Hyderabad (India) [ 61 ], iron ore mining in Pahang, Malaysia [ 69 ], in Anshan industrial city (Northeast China) [ 21 ], a municipal solid waste dump in Uyo (Nigeria) [ 62 ], paddy soils of Omor Rice Field, Nigeria [ 62 ], thallium mining area of southwest Guizhou (China) [ 50 ], Harran Plain (Turkey) [ 51 ], trailer park in Nigeria [ 28 ], a copper smelter in Khatoon Abad (Iran) (Nematollahi et al 2020), Houzhai River Watershed of Guizhou Province (China) [ 46 ], Kpone landfill site (Ghana) [ 63 ], wheat cultivated and natural soils of pastoral lands in the Bai Cheng Region (Xinjiang, China) [ 52 ], Zhundong mining area in Xinjiang [ 53 ], a Ramsar site (Deepor Beel) (Guwahati, India) [ 54 ], Panzhihua (China) [ 55 ], Southern Yunnan Province (China) [ 64 ], and the city of Lisbon (Portugal) [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Anthropogenically, the soil has been contaminated by fast industrial expansion and subsequent effluent discharge or exhaust emissions, agricultural fertilizers and pesticides, mining operations, population explosions, and subsequent urban dwelling pollution [6,[38][39][40][41][42][43][44][45]. Anthropogenic activities are generally regarded as being the primary source of PTEs in the soil in highly developed, urbanized and industrial urban areas [46][47][48][49], mining areas [5,[50][51][52], or agricultural sectors [41,53]. However, a large body of research on this subject supports the importance of the geological background in contributing to higher PTE contents in soil [2,[33][34][35][36][37]54,55].…”
Section: Introductionmentioning
confidence: 99%